Some Properties of Prequasi Normed Generalized de La Vallée Poussin's Mean Sequence Space. (11th May 2020) - Bakery, Awad A.; Mohammed, Mustafa M.
Abstract : In this article, we study some topological properties of the multiplication operator on generalized de La Vallée Poussin's mean sequence space equipped with the prequasi norm and the prequasi operator ideal generated by s -numbers and this sequence space.